Răspunsuri

2014-10-15T23:55:54+03:00
∆=b^2-4ac ∆=25-6*4=25-24=1 x1,2=(-b+,-√∆)/2a X1=(5-1)/2=2 X2=(5+1)/2=3 X^2-7x+10=0 ∆=49-40=9 √∆=3 x1=(7-3)/2=2 x2=(7+3)/2=5 X^2-5x+4=0 ∆=25-16=9 √∆=3 x1=(5-3)/2=1 x2=(5+3)/3=4
1 2 1
Cel mai inteligent răspuns!
2014-10-15T23:58:49+03:00
X²-5x+6=0 
Δ=b2-4ac=25-4*6=25-24=1
Δ>0 => x1,x2=-b +-√Δ
                           2a

√Δ= √1=1
X1=5+1 = 3
        2
x2=5-1 = 2

       2 x²-7x+10=0
 Δ=49-4*10*1=49-40=9
Δ>0 => x1,x2=-b +-√Δ
                           2a
√Δ=3

X1=7-3=2
      2

X2=7+3 =5
      2


x²-5x+4=0
Δ=25-4*4=25-16=9

Δ>0 => x1,x2=-b +-√Δ
                           2a
√Δ=3
X1=5-3 = 1
       2

X2=5+3=4
       2

2 5 2